ENHANCING THE EFFECTIVENESS OF TEACHING THE NUMBER SYSTEM IN 7TH-GRADE ALGEBRA THROUGH THE USE OF DIGITAL TECHNOLOGIES - Dzhaparova S. N.; Mamyrov J. M.; Anarbek kyzy A. (Vestnik Issyk-Kulʹskogo universiteta)
This article examines the use of digital technologies in teaching the number system in the 7th-grade algebra curriculum. Digital technologies increase students' interest in the subject and help them develop a deeper understanding of mathematical concepts. The study analyzes the potential for improving teaching effectiveness through interactive platforms, multimedia resources, and digital simulations. It also discusses the key advantages and possible challenges of using digital technologies and provides practical recommendations. Digital tools aid students in understanding fundamental mathematical concepts such as natural numbers, integers, rational, and irrational numbers. The use of digital technologies offers great opportunities for a deeper exploration of this topic and makes learning more engaging. The article explores methods for working with auxiliary programs for teaching the number system and their impact on students' academic performance. In conclusion, it is emphasized that the proper use of digital teaching methods enhances students' logical thinking and makes the learning process more engaging and accessible.